Hitam Putih PRRI-Permesta: Konvergensi Dua Kepentingan Berbeda 1956–1961 - Maulida, Faishal Hilmy (Paradigma: Jurnal Kajian Budaya, 2018)
Regional upheavals that occurred in Sumatra and Sulawesi in the period of 1956–1961 indicated a meeting point between two interests, i.e. the desire of the regions to get rights through regional autonomy and develop power to eradicate communism. This paper aimed at analysing regional upheavals involving PRRI-Permesta in terms of the meeting point between the two different interests. The method used in this study is a historical one. The results showed that the upheavals that arose from certain interests could not be accommodated by the central government, and this made the region take the initiative to solve them with military engagement. It can be concluded that PRRI-Permesta was an emerging movement in the region demanding reforms in the management of the state by the central government. The anti-communist characteristics of the movement made the United States of America ready to provide support for a movement against the central government. However, this also means that there was an encounter between two different interests in one vision of the struggle.